The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-08991-y
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between leg-to-leg bioelectrical Impedance analysis and computerized tomography in abdominal visceral fat measurement

Abstract: The aim of this study was to evaluate leg-to-leg bioelectrical impedance analysis (LBIA) using a four-contact electrode system for measuring abdominal visceral fat area (VFA). The present study recruited 381 (240 male and 141 female) Chinese participants to compare VFA measurements estimated by a standing LBIA system (VFALBIA) with computerized tomography (CT) scanned at the L4-L5 vertebrae (VFACT). The total mean body mass index (BMI) was 24.7 ± 4.2 kg/m2. Correlation analysis, regression analysis, Bland-Altm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Gomez et al and Park et al reported bioimpedance analysis tends to underestimate VFA compared with CT [2730]. Difference between VFA estimated by CT and BIA was large especially in the subjects with high BMI and large VFA estimated by CT [29, 30]. Our data with T2D patients are compatible to these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Gomez et al and Park et al reported bioimpedance analysis tends to underestimate VFA compared with CT [2730]. Difference between VFA estimated by CT and BIA was large especially in the subjects with high BMI and large VFA estimated by CT [29, 30]. Our data with T2D patients are compatible to these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Four studies with a total of 186 participants compared agreement between ultrasound and MRI or CT to quantify IAAT thickness. Of the studies that estimated IAAT area, comparator methods included DXA and several BIA techniques . The BIA estimation of IAAT was based on unpublished equations derived from the instrument manufacturers.…”
Section: Resultsmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is an alternative method for measuring body fat because it is fast, safe and non-invasive. 4,5,7,8 BIA showed a significant strong correlation with CT in measuring of VAT and SAT (r=0.89 and r=0.85, respectively) 6 and also with MRI in determining body fat and VAT (r=0.89 and r= 0.84, respectively). 9 Nitric oxide (NO) is a signaling and free radical molecule.…”
Section: Introductionmentioning
confidence: 85%